St. Kitts and Nevis : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper reviews economic developments in St. Kitts and Nevis during 1993-95. Economic performance was broadly satisfactory in 1993-94 with high real GDP growth, low inflation, and a favorable external position. Faced with increased external competition and reduced concessional aid flows, the government has pursued a development strategy aimed at diversifying the economy away from the sugar industry toward tourism-led activities. As a result, the tourism sector expanded rapidly, generating substantial employment opportunities and foreign exchange earnings, the economic structure being centered on service-oriented activities.